Noninvasive Imaging of Immune Checkpoint Ligand PD-L1 in Tumors and Metastases for Guiding Immunotherapy - Samit Chatterjee PhD; Wojciech G. Lesniak PhD; Sridhar Nimmagadda PhD (Molecular Imaging, 2017)
Immunotherapy holds great promise in cancer treatment. The challenges in advancing immunotherapies lie in patient stratification and monitoring therapy. Noninvasive detection of immune checkpoint ligand PD-L1 can serve as an important biomarker for guidance and monitoring of immunotherapy. Here in, we provide an overview of our efforts to develop clinically translatable PD-L1-specific imaging agents for quantitative and real-time assessment of PD-L1 expression in tumor microenvironment.